Does it matter if students procrastinate more in some courses than in others? A multilevel perspective on procrastination and academic achievement. (December 2018) - Kljajic, Kristina; Gaudreau, Patrick
Abstract: We proposed and tested a novel multilevel perspective on procrastination by examining the prospective relation between procrastination and grades across students (i.e., between-person level) and across the courses taken by each student (i.e., within-person level). A sample of 208 university students completed repeated measures of procrastination for each of their courses during the semester and the official final grades were obtained at the end of the semester. The results of multilevel modeling revealed that students who procrastinated more than other students received lower grades than these students (i.e., between-person level). Moreover, the results revealed that in the courses in which students procrastinated more than their own average, they received lower grades than their own average (i.e., within-person level). These findings build upon past findings on procrastination across students while also moving this research field forward by offering a new understanding of procrastination as a within-person risk factor for academic difficulties. Highlights: We proposed and tested a novel multilevel perspective on procrastination. We measured procrastination and grades in each course taken by each student. Procrastination was negatively associated with grades at two levels of analysis. This association remained significant after adding relevant control variables. The findings underscore the value of multilevel modeling in personality research.